(untitled) (Global Journal of Science Frontier Research, 2019)
Amazingly, helium nano-droplets and the same torus-shaped fast spinning nonlinear electromagnetic fields (NEMFs) with the dynamics. The fact that our Sun changes its magnetic as periodic flipping of the magnetic poles of the Sun) actually means periodic directions of spinning of the nonlinear spins clockwise like a vortex, it sucks energy in through both the axis of spinning. This speeds the sun’s spinning, which bulges the Sun at the increases the turbulent activity there, making the counterclockwise as an anti-vortex, it loses energy out through its magne as a lemon, shrinks the equatorial area, and ceases observed periodic switches of high and low activity of our Sun (and also of helium droplets). The article offers a dynamic model low solar activity.